Human capital as a factor of sustainable development in the conditions of modern social risks - Olga Mikhailovna Komornikova (Вестник Майкопского государственного технологического университета, 2023)
Modern society is faced with a number of potentially new risks, the opposition to which actualizes the need for a personality possessing intellectual and spiritual qualities, united in the concept of “human capital”. The work is based on interdisciplinary, sociocultural and activity approaches. The question of the significance of a number of personality characteristics for social development was developed thoroughly in the works of philosophers and sociologists for more than a century, but remains relevant only at the theoretical level for a tiny number of people. In the real life of society these characteristics are rarely realized. The ideal created by the intellectual elite is not shared by the majority of the population. The significance of the concept of “human capital” is due to the fact that it focuses on bridging the gap between the theoretical concepts and real social practices, since this gap creates risks for both individual communities and humanity as a whole. The intellectual component of human capital includes knowledge of social processes, operational capabilities of thinking, which are getting more complicated from era to era. The spiritual component is meaningfully filled with humanistic values, an understanding of the interconnectedness and interdependence of individuals and their communities, the need for socially responsible actions.